Coronary microvascular dysfunction may be related to IGF-1 in acromegalic patients and can be restored by therapy. (February 2018) - Tellatin, Sara; Maffei, Pietro; Osto, Elena; Dassie, Francesca; Famoso, Giulia; Montisci, Roberta; Martini, Chiara; Fallo, Francesco; Marra, Martina Perazzolo; Mioni, Roberto; Iliceto, Sabino; Vettor, Roberto; et al.
Abstract: Background and aims: Acromegaly increases the risk of cardiovascular mortality. Data on the cardiovascular risk in asymptomatic acromegaly are limited. In particular, data on coronary microvascular abnormalities are lacking. We assessed coronary flow reserve (CFR) as a marker of coronary microvascular function in asymptomatic acromegaly. Methods: We studied 40 acromegalic patients (23 male, age 52 ± 11 years) without clinical evidence of cardiovascular disease, and 40 control subjects matched for age and sex. Coronary flow velocity in the left anterior descending coronary artery was detected by transthoracic Doppler echocardiography, at rest, and during adenosine infusion. CFR was the ratio of hyperaemic to resting diastolic flow velocity. Results: CFR was lower in patients than in controls (2.9 ± 0.8 vs . 3.7 ± 0.6, p  < 0.0001) and was abnormal (≤2.5) in 13 patients (32.5%) compared with any control subjects (0%) ( p  < 0.0001). CFR was inversely related to insulin-like growth factor 1 (IGF-1) levels (r = −0.5, p  < 0.004). In patients with CFR≤2.5, IGF-1 was higher (756 [381–898] μg/l versus 246 [186–484] μg/l, p  < 0.007) whereas growth hormone (GH) levels were similar (6.3 [2.8–13.7] μg/l versus 5 [2.8–8.9] μg/l, p  = 0.8). In multivariable linear regression analysis, IGF-1 was independently associated with CFR ( p  < 0.0001). In multiple logistic regression analysis, IGF-1 independently increased the probability of CFR≤2.5 ( p  = 0.009). In four patients with active disease (all with CFR<2.5), treatment with somatostatin analogues normalized CFR. However the other four patients with active disease were not responder. Conclusions: Acromegalic patients have coronary microvascular dysfunction that may be restored by therapy with somatostatin analogues. IGF-1 independently correlates with the coronary microvascular impairment, suggesting the pivotal role of this hormone in explaining the increased cardiovascular risk in acromegaly. Highlights: Acromegaly increases the risk of cardiovascular mortality. We aimed to determine the influence of acromegaly on coronary microvascular function. We studied 40 acromegalic patients without clinical evidence of cardiovascular disease. We assessed coronary flow reserve as a marker of coronary microvascular function. IGF-1 independently correlates with the coronary microvascular impairment.